The Land and The Sources of Livelihood for the Sakai Tribe in Bathin Solapan District, Bengkalis Regency - Asriwandari, Hesti; Jalil, Ashaluddin; Hidir, Achmad; Bahri, Syamsul; Yesi; Sugiyanto, Seger (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
This research aims to describe the existing life of the Sakai Tribe in the context of land use and natural resources. The method used was qualitative by interviewing village government, traditional leaders, women's leaders, and youth leaders. The results of this research found that the source of the problems that are faced by the Sakai Tribe came from unequal control of the land and the natural resources. Besides it is not unbalanced, there is also an element of control that was carried out without legal means. The natural resources and the resources that were previously abundant and used for the livelihood of the Sakai tribe are gradually being controlled by the companies and the residents outside the Sakai traditional community. This condition causes their sociocultural system to experience changes with fading collective values becoming individualistic in the context of the use of natural resources. The conditions experienced by the Sakai Tribe need to be a concern to the stakeholders. They need social policy intervention to fulfill and protect the rights of indigenous peoples as regulated by the constitution.